Divergência em GPU: análises e alocação de registradores - Diogo Nunes Sampaio (2013)
The use of graphics processing units (GPUs) for accelerating Data Parallel workloads is the new trend on the computing market. This growing interest brought renewed attention to the Single Instruction Multiple Data (SIMD) execution model. SIMD machines give application developers tremendous computational power; however, programmingthem is stil challenging. In particular, developers must deal with memory and control flow divergences. These phenomena stem from a condition that we call data divergence, which occurs whenever processing elements (PEs) that run in lockstep see the same variable name holding different values. To deal with divergences this work introduces a new code analysis, called Divergence Analysis with Affine Constraints. Application developers and compilers can benefit from the information generated by this analysis with two different objectives. First, to improve code generate to machines that have vector instructions but cannot handle control divergence. Second, to optimize GPU code. To illustrate the last one, we present register allocators that relly on divergenceinformation to better use GPU memory hierarchy. These optimized allocators produced GPU code that is 29.70% faster than the code produced by a conventional allocator when tested on a suite of well-known benchmarks.